Flood Evacuation Mapping in Parit Raja, Batu Pahat, Johor - Mohd Ali, Nur Afni; Haji Abustan, Muhammad Salleh (Recent Trends in Civil Engineering and Built Environment, 2024)
Floods are a sort of calamity that occurs on a yearly basis in Malaysia. Many beneficial solutions, such as dam construction, were studied in order to prevent the flood from reoccurring. Unfortunately, this sort of solution has become one of the causes of floods. When the Sembrong Dam broke in the Parit Raja region, a similar event may have occurred. The time limit for evacuation should be studied to determine the safest timeframe for evacuation to the designated destination. Flood mapping that illustrates the escape route must be made public in order to alert residents in the flood-prone region. Furthermore, comparing numerous ranges of walking velocity is critical, since different age groups have different walking speeds to simulate in developing evacuation simulations that result in extremely detailed evacuation mapping. Evacuation Mapping is one of the many approaches that should be considered while planning for future floods. Flood Evacuation Mapping for any suitable and recognised sites that may be prone to recurrent flooding, particularly in the event of a dam failure.